2019
DOI: 10.3390/lubricants7110101
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Ethanol with Friction Modifiers in Model Engine Lubricants

Abstract: When employed as an engine fuel, ethanol can accumulate in the lubricant during use. Previous work has shown that ethanol contamination affects friction and elastohydrodynamic lubrication (EHL) film formation, and also the growth and stability of anti-wear tribofilms. The present work uses spacer-layer ultrathin interferometry and MTM tests to investigate how ethanol (both hydrated and anhydrous) interacts with friction modifiers in model lubricants. Small proportions (5 wt %) of ethanol were added to solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Viscosity reduction due to fuel dilution has been observed by several researchers in both field [24,29] and lab tests [32][33][34], which is mostly due to the much lower viscosity of ethanol in comparison to usual engine lubricants. On the one hand, engine tests comparing gasoline and gasoline with different concentrations of ethanol showed that viscosity reduction over time depends much more on the lubricant type than the fuel type, as both gasoline and ethanol have much lower viscosity than engine lubricants [24].…”
Section: Effect Of Ethanol Fuel On Lubricant's Physicochemical Proper...mentioning
confidence: 96%
See 1 more Smart Citation
“…Viscosity reduction due to fuel dilution has been observed by several researchers in both field [24,29] and lab tests [32][33][34], which is mostly due to the much lower viscosity of ethanol in comparison to usual engine lubricants. On the one hand, engine tests comparing gasoline and gasoline with different concentrations of ethanol showed that viscosity reduction over time depends much more on the lubricant type than the fuel type, as both gasoline and ethanol have much lower viscosity than engine lubricants [24].…”
Section: Effect Of Ethanol Fuel On Lubricant's Physicochemical Proper...mentioning
confidence: 96%
“…Attempts to run laboratory tests with a mixture of ethanol and lubricant, such as those described in previous paragraphs, usually require attention to the test temperature. The selection of temperatures above the evaporation point of ethanol (around 69 • C) may result in quick ethanol evaporation which, while it may not invalidate the test, needs to be considered during analysis of the results [32][33][34]40]. As an alternative, in a study of the tribological impact of ethanol Lenauer, et al [43] conducted an artificial engine oil alteration process with addition of ethanol combustion products to the oil, which was later used in reciprocating sliding laboratory tests.…”
Section: General Trend Of the Impact Of Ethanol On Friction And Wearmentioning
confidence: 99%
“…Moreover, atomic force microscopy (AFM) studies conducted by Barthel et al 29 revealed that ethanol cleaning and its evaporatively deposited residues exhibited superior boundary lubrication, antifriction, and antiwear properties than UV/ozone cleaned surfaces. In addition, Costa et al 30 investigated the interaction between lubricating oil and ethanol (5 wt %) and discovered that ethanol increased the thickness of the boundary film of the organic friction modifier, thereby decreasing the boundary friction. Liu et al 31 achieved macroscopic superlubricity with basil seed gel (BSG)−ethanol (1:1), primarily because the mechanical strength of the adsorption layer was enhanced when the ethanol molecules entered the BSG network, and the lubricating film was prevented from being destroyed during the sliding process.…”
Section: Introductionmentioning
confidence: 99%
“…Since ethanol can be used as a biofuel additive, several researchers have examined its effect on friction and wear, whereas petroleum ether and acetone have been the subject of very few comparable studies. Using DFT, Barnette et al investigated the friction and wear behavior of a SiO 2 surface in a 50% humidity and ethanol vapor environment.…”
Section: Introductionmentioning
confidence: 99%
“…Uma importante classe de aditivos modificadores de atrito são os compostos de molibdênio tais como o dialquilditiocarbamato de molibdênio (MoDTC), o qual se descompõe em condições de alta tensão de cisalhamento e temperatura, formando sobre a superfície deslizante um tribofilme rico em MoS2. A capacidade de redução de atrito deste aditivo já foi mostrada em diferentes trabalhos, apresentando reduções no valor de coeficiente de atrito de valores acima de 0,11 para valores tão baixos como 0,04 a 0,08 (BALARINI et al, 2020;DE BARROS'BOUCHET et al, 2005;ERDEMIR, 2005 SPIKES, 2019SPIKES, , 2016KHUONG et al, 2017;RUIZ, 2014). Apesar dos estudos realizados, ainda são escassos os conhecimentos em relação aos efeitos que o etanol causa nos tribofilmes formados pelos aditivos usados em óleos de motor, e a maioria destes trabalhos tem sido focados nos efeitos deste combustível no aditivo anti-desgaste ZDDP.…”
Section: Listas De Figurasunclassified